The German CPU registry: comparison of smokers and nonsmokers - Bock, Daniel Günter; Senges, Jochen; Pohlmann, C.; Hochadel, Matthias; Münzel, Thomas; Giannitsis, Evangelos; Schmitt, C.; Heusch, Gerd; Voigtländer, Theda; Mudra, H.; Schumacher, B.; Darius, H.; et al. (Herz, 2020)
Chest pain is a major reason for admission to an internal emergency department, and smoking is a well-known risk factor for coronary artery disease (CAD) and acute coronary syndrome (ACS). The aim of this analysis is to illustrate the differences between smokers and nonsmokers presenting to German chest pain units (CPU) in regard to patient characteristics, CAD manifestation, treatment strategy, and prognosis.
Published: 27 July 2018
Gesehen am 17.06.2020